Does Executive Compensation Moderate the Impact of Ownership Structure and CEO Characteristics on Earnings Management? Evidence from Indonesian Manufacturing Companies - Hamdani; Imam Hidayat; Sustari Alamsyah; Dhea Zatira; Eni Suharti; Sonia Nadia Muslimah; Hendra Galuh Febrianto (IECON: International Economics and Business Conference, 2025)
This study addresses the urgent need to understand how corporate governance mechanisms influence earnings management practices in emerging markets. The research aims to examine the effects of public ownership, female CEOs, ethnic CEOs, and managerial ownership on earnings management, with executive compensation as a moderating variable. Using panel data regression analysis with Eviews 12 on 25 manufacturing companies listed on the Indonesia Stock Exchange (2019-2023), this study employs purposive sampling technique. Findings reveal that female CEOs and ethnic CEOs significantly influence earnings management, while public ownership and managerial ownership show no significant effects. Executive compensation effectively moderates the relationships between female/ethnic CEOs and earnings management, but fails to moderate public and managerial ownership effects. This research contributes to corporate governance literature by integrating demographic diversity and ownership structure perspectives, providing novel insights into how executive characteristics and compensation schemes interact to shape financial reporting practices in emerging market contexts, offering practical implications for regulatory frameworks and corporate policy design.